Recensione a P. Foote (ed), Olaus Magnus, A Description of the Northen People, London 1998 - Abbamonte, Giancarlo (Classiconorroena, 2016)
Recensione a P. Foote (ed), Olaus Magnus, A Description of the Northen People, London 1998